Analysis of The Effect of Service Quality, Product Quality, and Price on Customer Loyalty at Seis Coffee with Customer Satisfaction as an Intervening Variable - Arby Prawira , Muhammad; Sembiring, Paham Ginting; Rini, Endang Sulistya (Indonesian Journal Publisher, 2025)
The purpose of this study was to determine the effect of service quality, product quality, and price on customer satisfaction at Seis Coffee. To determine the effect of service quality, product quality, price, and customer satisfaction on consumer loyalty at Seis Coffee. To determine the effect of service quality, product quality, and price on consumer loyalty and customer satisfaction as intervening variables at Seis Coffee. The theories considered relevant in this study are service quality, product quality, price, customer satisfaction, and consumer loyalty. This study is a quantitative study using SPSS research techniques. The population in this study was Seis Coffee customers taken during the last 3 months, namely April to June 2025, as many as 1051 respondents, and the research sample obtained was 91 people using the Slovin formula with a precision of 10% with a confidence level of 90%. The data collection technique in this study was by distributing questionnaires. The data analysis technique in this study used multiple linear regression analysis and hypothesis testing using the SPSS program. The results showed that service quality did not have a significant effect on customer satisfaction, product quality had a positive and significant effect on customer satisfaction, and price had a positive and significant effect on customer satisfaction. Service quality did not affect consumer loyalty, product quality did not affect consumer loyalty, price had a positive and significant effect on consumer loyalty, and customer satisfaction had a positive and significant effect on consumer loyalty. The results of the Sobel test showed that customer satisfaction did not significantly mediate the effect of service quality on consumer loyalty. Customer satisfaction did not significantly mediate the effect of product quality on consumer loyalty, and customer satisfaction did not significantly mediate the effect of price on consumer loyalty.